2023
DOI: 10.1007/s12525-023-00654-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting anomalous cryptocurrency transactions: An AML/CFT application of machine learning-based forensics

Abstract: In shaping the Internet of Money, the application of blockchain and distributed ledger technologies (DLTs) to the financial sector triggered regulatory concerns. Notably, while the user anonymity enabled in this field may safeguard privacy and data protection, the lack of identifiability hinders accountability and challenges the fight against money laundering and the financing of terrorism and proliferation (AML/CFT). As law enforcement agencies and the private sector apply forensics to track crypto transfers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 62 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Support Vector Machine, are used to improve the accuracy of fraud detection. All these algorithms combined creates a robust framework for attacking money laundering (Pavlidis, 2023;Pocher et al, 2022). Ruchay et al (2023) confirmed the identification of suspicious transactions using the random forest algorithm and demonstrated its effectiveness through an accuracy rate of 99%.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Support Vector Machine, are used to improve the accuracy of fraud detection. All these algorithms combined creates a robust framework for attacking money laundering (Pavlidis, 2023;Pocher et al, 2022). Ruchay et al (2023) confirmed the identification of suspicious transactions using the random forest algorithm and demonstrated its effectiveness through an accuracy rate of 99%.…”
Section: Resultsmentioning
confidence: 79%
“…This reflects the popularity of machine learning in financial data analysis and its ability to Tree is one of the most frequently used algorithms with four appearances, demonstrating its effectiveness in understanding and classifying financial transaction patterns (Alkhalili et al, 2021;Kanamori et al, 2022;Masrom et al, 2023;Ruiz & Angelis, 2022). Furthermore, Graph Convolutional Networks (GCN) and Graph Attention Networks (GAT) appeared three times each, underlining the importance of graph network analysis in suspicious activity detection (Naveed et al, 2023a;Pocher et al, 2022;Song & Gu, 2023). Random Forest, Support Vector Machine, and Gradient Boosted Tree each appeared three times, showing their prevalence and effectiveness in dealing with complex financial data (Alkhalili et al, 2021;Alotibi et al, 2022;Labanca et al, 2022;Masrom et al, 2023;Ruiz & Angelis, 2022;Pocher et al, 2022;Ruchay et al, 2023;Zhang & Trubey, 2019) .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…First is the integration of blockchain technology into cloud forensics, offering methods and architectures that enhance the credibility, effectiveness, and security of forensic investigations in digital environments mostly related to the chain of custody (CoC). The central focus of [3][4][5][6][7][8][9][10][11][12][13][14][15] was the utilization of blockchain technology for ensuring the integrity, traceability, and privacy of digital evidence and CoC in digital forensics. Some of the solutions for specific use cases such as image forensics, healthcare, and finance were generally discussed, as well as blockchain integration with computer forensics in the context of CoC.…”
Section: Chain-of-custody Integration With Blockchainmentioning
confidence: 99%
“…An emergent trend in cryptocurrency forensics has been the leveraging of machine learning algorithms for blockchain data evaluation. These algorithms have exhibited proficiency in unveiling patterns of suspicious activity and forecasting impending deceptive transactions [12,24]. Their prowess extends to handling vast data sets, uncovering correlations potentially elusive to human investigators.…”
Section: Figure 3 Blockchain Forensics Investigationmentioning
confidence: 99%